The infusion speech skeleton application (Apps) concept as a teaching medium for office management & technology (OMT) students / Shamsinar Ibrahim … [et al.] - Ibrahim, Shamsinar; Abas, Nurliyana; Hashim, Norhafiza; Shawalludin, Syahrini (Universiti Teknologi MARA, 2021)
This research aims to employ Apps in public speaking courses to facilitate OMT students' learning process with simplified speech draft development versions. The Apps development was categorized into two divisions: (i) content and (ii) design and concept. Specifically, Apps content served to complement OMT students' requirements while Apps design and concept encompassed interactive designs and waterfall models. Additionally, Analysis, Design, Development, Implementation, and Evaluation (ADDIE) and focus group discussion (FGD) were incorporated as research methodologies. Although App utilization was presented in multiple educational courses, this study pioneered App development and implementation in the public speaking courses in line with non-communication (OMT ) student needs